εPKC confers acute tolerance to cerebral ischemic reperfusion injury - Bright, Rachel (2008)
In response to mild ischemic stress, the brain elicits endogenous survival mechanisms to protect cells against a subsequent lethal ischemic stress, referred to as ischemic tolerance. The molecular signals that mediate this protection are thought to involve the expression and activation of multiple kinases, including protein kinase C (PKC). Here we demonstrate that εPKC mediates cerebral ischemic tolerance in vivo. Systemic delivery of ψεRACK, an εPKC-selective peptide activator, confers neuroprotection against a subsequent cerebral ischemic event when delivered immediately prior to stroke. In addition, activation of εPKC by ψεRACK treatment decreases vascular tone in vivo, as demonstrated by a reduction in microvascular cerebral blood flow. Here we demonstrate the role of acute and transient εPKC in early cerebral tolerance in vivo and suggest that extra-parenchymal mechanisms, such as vasoconstriction, may contribute to the conferred protection.